2015
DOI: 10.1016/j.engstruct.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a rolling isolation system using reduced order structural models

Abstract: a b s t r a c tThis paper examines the performances of lightly-and heavily-damped rolling isolation systems (RISs) located within earthquake-excited structures. Six steel structures of varying height and stiffness are selected so as to represent a range of potential RIS installations. Computation models of representative frames from each of the six structures are reduced through dynamic condensation and assembled with models for biaxial isotropic hysteretic behavior within each floor. A novel reduced order mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Harvey and Gavin found that a uniaxial numerical model was unable to predict the chaotic responses of a four-bowl supported system [14]. However, they later found that even a reducedorder numerical model was validated as correct when compared with the test results [15], when all of the initial conditions were fully considered [16]. Ortiz et al also found that the numerical results could be close to the experimental results for a rolling-bearing supported building [17].…”
Section: Introductionmentioning
confidence: 95%
“…Harvey and Gavin found that a uniaxial numerical model was unable to predict the chaotic responses of a four-bowl supported system [14]. However, they later found that even a reducedorder numerical model was validated as correct when compared with the test results [15], when all of the initial conditions were fully considered [16]. Ortiz et al also found that the numerical results could be close to the experimental results for a rolling-bearing supported building [17].…”
Section: Introductionmentioning
confidence: 95%
“…The principle of operation is basically the same: The horizontal components of the ground (or floor) movement are mechanically separated from the isolated structure (or equipment) through compatible, sliding, rotating, or rolling interfaces . In rolling isolation systems proposed by Harvey and Gavin, Harvey et al and Harvey and Gavin, the limited rolling of steel spheres encapsulated between convex surfaces is employed in order to confine the displacement of the ball by means of a lip located at the border of every rolling surface. The roll‐n‐cage isolators limit the peak isolator displacements and prevent PADJS under strong seismic excitation by using a self‐braking mechanism, which contains the pounding inside the roll‐n‐cage isolator's frame.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, more frictional devices with a long service life have been developed. For example, Harvey and Gavin [7] proposed double rolling isolation systems (RISs). They found that the friction-based isolation devices had perfect seismic isolation performance, long service lives and low cost [2].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the discussions above, the friction component was better than the viscous damping component, except that the frictional action prevented the structure from moving back to the initial site after earthquakes. After investigating the uniform friction distribution, the convex friction distribution and other variable friction distributions in space [1][2][3][4][5][6][7][8][9], it had a summary that a spatially concave friction distribution, combining with an appropriate spring component, would not prevent the structural restoration [10]. As for the spatially concave friction distribution, the friction coefficient has the smallest value in the contact center, and increases when the structure moves away from the contact center.…”
Section: Introductionmentioning
confidence: 99%